Random forest model analysis of influencing factors of chemotherapy-induced peripheral neuropathy in patients with nasopharyngeal carcinoma: a cross-sectional survey study - Zhang, Yanxin; Huang, Xiaojun; Yang, Guirong; Li, Wei; Liang, Limin; Wei, Lina; Lu, Jiamei (Frontiers in Oncology, 2025)
BackgroundChemotherapy-induced peripheral neuropathy (CIPN) is a progressive and persistent condition that can significantly affect the quality of life of patients. Even after the cessation of chemotherapy, symptoms of CIPN may endure for an extended period. Despite its considerable impact, there is a paucity of research examining the effects of CIPN on patients.ObjectiveTo investigate the current status of CIPN in patients with nasopharyngeal carcinoma (NPC) and accurately identify factors influencing neurotoxicity based on the Random Forest algorithm.MethodA total of 289 patients with NPC were admitted to the Radiotherapy Department of the First Affiliated Hospital of Guangxi Medical University between August 2023 and April 2024 to investigate the current status of neurotoxicity, cognitive impairment, fatigue, and hand-foot syndrome. To rank the importance of the influencing factors of CIPN in NPC patients, a random forest model was constructed to analyze the influencing factors.ResultsThe incidence of CIPN in NPC patients was 81.7%. The results of the random forest algorithm showed that age, chemotherapy cycle, tumor stage, chemotherapy regimen, concurrent chemoradiotherapy, BMI, hand and foot syndrome fatigue, and cognitive dysfunction were the main factors affecting CIPN in NPC patients (P<0.05).ConclusionThere is an urgent need to accurately identify the risk factors for CIPN in patients with NPC and develop multidisciplinary collaborative prevention and intervention measures to achieve effective prevention and comprehensive management.